On one type of pedagogical situations: classification and practical aspects - Victoria V. Dobrova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
On the basis of the previous theoretical research conducted by the author, in this paper the concept of pedagogical situation in described in connection with the concept of pedagogical event. The classification of pedagogical situations presented in the paper is based on the possibility and ability of a pedagogical situation to reach a pedagogical problem, to achieve a pedagogical effect and thus to become a pedagogical event. On the basis of these grounds as well as the logic and practice of a teacher's everyday work, the three types of situations were identified. The first of them, that is a pedagogical situation in which the goal is achievable, which means that the situation can change from a potential situation to an actual situation, is described in the paper. The goal-oriented principle of analysis opens up the prospect of establishing relationships between all the parameters of the situation and the personal characteristics of its participants. The scheme for describing pedagogical situations logically includes the following components: participants (teachers and students a potential pedagogical agent), goal/task, conditions (locus).